2002
DOI: 10.19173/irrodl.v3i1.82
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation vs. Deliberation: CMC and the Problem of Argument in International Distance Education

Abstract: The idea that Internet-based distance education offers the potential to globalize higher education has not been matched by significant interest in the pedagogical and methodological issues at stake. This essay discusses a two-year experimental course conducted between two college classes in Karlskrona, Sweden and Ohio, in the United States. The goal of this course was to use online debate to augment intercultural understanding. This experiment involved both synchronous and asynchronous computer mediated confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…(1998, p. 397) From a catalogue of similar quotations, we selected this one from Marttunen because of his sustained program of research in this area (Marttunen, 1998;Marttunen & Laurinen, 2002). His results are not unique (Bonk & Cunningham, 1998;Bullen, 1999;Davis & Rouzie, 2002;De Laat, 2001;Gunawardena et al, 2001;Jeong, 2004;Lopez-Islas, 2001;McLaughlin & Luca, 2000;Pena-Shaff et al, 2001;Pena-Shaff & Nicholls, 2004;Rovai & Barnum, 2003;Thomas, 2002;Wilson, Varnhagen, Krupa, Kasprzak, Hunting, & Taylor, 2003;Yakimovicz & Murphy, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1998, p. 397) From a catalogue of similar quotations, we selected this one from Marttunen because of his sustained program of research in this area (Marttunen, 1998;Marttunen & Laurinen, 2002). His results are not unique (Bonk & Cunningham, 1998;Bullen, 1999;Davis & Rouzie, 2002;De Laat, 2001;Gunawardena et al, 2001;Jeong, 2004;Lopez-Islas, 2001;McLaughlin & Luca, 2000;Pena-Shaff et al, 2001;Pena-Shaff & Nicholls, 2004;Rovai & Barnum, 2003;Thomas, 2002;Wilson, Varnhagen, Krupa, Kasprzak, Hunting, & Taylor, 2003;Yakimovicz & Murphy, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors have observed a dissociation in threaded conversations between the temporal order of messages and the thread order of messages (Davis & Rouzie, 2002;Herring, 1999). This dissociation is caused by the fact that in most threaded visualization tools, the factors of space and time are dislocated.…”
Section: Sequential Incoherencementioning
confidence: 99%
“…In this sense Davis and Rouzie (Davis & Rouzie, 2002) note " as messages can be added to any node in a thread at any later date, students often failed to follow the development of a particular debate"; Also, sorting messages by time doesn't allow regarding the actual placement of a message in the threads.…”
Section: Sequential Incoherencementioning
confidence: 99%
“…Regarding the first dissociation, in threaded conversations, several authors have observed a dissociation between two possible views in current FTTs: the temporal and the thread order of messages [2,6]. This dissociation is caused by the dislocation of the factors of space and time in most of the threaded conversation visualizations.…”
Section: Anomalies In Vlcsmentioning
confidence: 99%
“…This dislocation makes conversations not as seamless as they should be: sorting by threads makes the tracking of timely exchanges difficult. Along these lines, Davis and Rouzie [2] note "as messages can be added to any node in a thread at any later date, students often failed to follow the development of a particular debate" [2, p.12]. But sorting messages by time does not allow users to regard the actual placement of a message in the threads.…”
Section: Anomalies In Vlcsmentioning
confidence: 99%